Formulasi Nugget Berbahan Dasar Ikan Terbang (Parexocoetus brachypterus), Tepung Jewawut (Setaria italica (L.) Beauv.) dan Daun Kelor (Moringa oleifera) Sebagai Menu PMT Pencegah Stunting - Ismail, Ayu Indayanti; Yuniati, Dewi; Aryanti, Novi (Journal Galung Tropika, 2023)
The high prevalence rate of stunting in West Sulawesi Province, which reached 33.8, places West Sulawesi in second place in the province with the highest stunting in Indonesia. One effort to prevent stunting is to diversify the intake of complementary foods for children aged 6-23 months by utilizing local natural resources. This research aims to formulate flying fish, barley flour, and Moringa leaves as a functional food in processed nuggets as a menu for Supplementary Feeding (PMT) for babies under two years old. The research method was carried out in three stages, namely, the nugget formulation in two formulas, namely F1 and F2. Next, an organoleptic test is carried out to select the best formula, followed by a nutritional content analysis, which includes proximate analysis and mineral testing. The research results showed that the nugget formula selected was based on organoleptic tests on 30 panelists, namely F1 nuggets with a mixture of 175 g of flying fish, 75 g of barley flour, and 10 g of moringa leaves. These nuggets contain nutrients per 100 grams, namely protein 14.36 g, carbohydrates 27.83 g, fat 5.53 g, crude fiber 1.22 g, iron 62.78 mg/kg, calcium 97.53 mg/kg, and zinc 15.52 mg/kg. Therefore, nuggets with the selected formula are rich in the nutrients needed in complementary breast milk foods to prevent stunting.